A new model of performance classification to standardize the research results in swimming. Issue 4 (3rd April 2023) - Ruiz-Navarro, Jesús J.; López-Belmonte, Óscar; Gay, Ana; Cuenca-Fernández, Francisco; Arellano, Raúl
ABSTRACT: The level of expertise must be defined for the sample studied when reporting research in sport. Concretely in swimming, apart from the participants' background, the competitive status is based on the level that swimmers participate. Thus, the International Swimming Federation (FINA) points are added to improve the sample level characterization. The aim of this study was two-fold: (1) to assess whether national and regional swimmers from different countries differ in their performance level (based on FINA points), and (2) to propose a model that allows standardizing the research results in swimming. The FINA points of 5876 participants (males = 2962 and females = 2914) in 100 m butterfly, backstroke, breaststroke and freestyle were retrieved from nationals ( n = 21) and regionals ( n = 44) swimming competitions. One-way analysis of variance was conducted to test the difference in FINA points between swimmers of different countries. Significant disparities (100–350 FINA points; p < 0.001) were observed in national and regional competitions for male and female swimmers among the different countries analyzed. This could lead to misleading conclusions when comparing studies with national or regional swimmers from different countries. In this regard, a new model of performance classification based on national and regional worldwide competition is proposed. This might be used to standardized the swimming research results. Highlights - The current classification of swimmers' status could lead to misleading conclusion when comparing studies from different countries using national or regional swimmers. - The proposed model will allow to better standardize the research results in swimming, aiding to draw more accurate conclusion when comparing results from different studies.